Role of Insulin Like Growth Factor (IGF) in Lung Cancer with Underlying Diabetes Melitus - Andayani, Novita; Mauliza (Journal of Medical Science, 2023)
Lung cancer is one of the diseases which the highest incidence and mortality in the world. Lung cancer consists of small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) with various subtypes. Diabetes mellitus is one of the comorbidities that is often found in lung cancer patients, which is around 6% - 18% in lung cancer patients. Diabetes is a comorbidity factor that has a serious effect in increasing cancer cell progressivity through the activity of insulin growth factor (IGF) which consists of receptors (IGF-R) and binding proteins (IGFP). The role of IGF produces oncogenic mutations at the DNA level with the process of lung cancer immunity stimulates mitogenesis initiated by insulin and initiates neoplasm cells. IGF receptor mechanism has antineoplastic properties, to fulfill glycemia control that will reduce lung cancer progressivity and prevent clinical worsening so that it can help reduce lung cancer mortality with oral hypoglycemia drugs along with lung cancer therapy modalities such as cytotoxic agents, radiotherapy, immunotherapy, and surgery. The role of IGF is to amplify insulin levels in glucose, lipid, and protein metabolism. IGF can induce cell differentiation and initiation of neoplasm. Diabetes mellitus as a comorbidity can poor clinical outcomes and promote progression through IGF receptor activation in the tumorigenesis process.